2021
DOI: 10.1038/s42003-021-01975-9
|View full text |Cite|
|
Sign up to set email alerts
|

RNAi efficacy is enhanced by chronic dsRNA feeding in pollen beetle

Abstract: Double-stranded RNAs (dsRNAs) represent a promising class of biosafe insecticidal compounds. We examined the ability to induce RNA interference (RNAi) in the pollen beetle Brassicogethes aeneus via anther feeding, and compared short-term (3 d) to chronic (17 d) feeding of various concentrations of dsRNA targeting αCOP (dsαCOP). In short-term dsαCOP feeding, only the highest concentration resulted in significant reductions in B. aeneus survival; whereas in chronic dsαCOP feeding, all three concentrations result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 41 publications
0
13
0
2
Order By: Relevance
“… Knorr et al (2018) observed at least 90% adult B. aeneus mortality after 14 days, in all four target gene treatments examined, after dietary exposure to water containing 1 μg dsRNA/μl followed by continuous uptake of dsRNA in artificial diet containing 500 ng/cm 2 . Willow et al (2020 , 2021a , b , c) examined RNAi sensitivity in B. aeneus via multiple field-relevant routes of exposure, and in both adults and larvae. A SIGS approach to achieving RNAi-induced mortality in B. aeneus , via feeding on dsRNA-treated oilseed rape buds and anthers, leads to variable success in achieving a lethal phenotype in this pest species.…”
Section: Observed Rnai Sensitivities In Coleopteramentioning
confidence: 99%
“… Knorr et al (2018) observed at least 90% adult B. aeneus mortality after 14 days, in all four target gene treatments examined, after dietary exposure to water containing 1 μg dsRNA/μl followed by continuous uptake of dsRNA in artificial diet containing 500 ng/cm 2 . Willow et al (2020 , 2021a , b , c) examined RNAi sensitivity in B. aeneus via multiple field-relevant routes of exposure, and in both adults and larvae. A SIGS approach to achieving RNAi-induced mortality in B. aeneus , via feeding on dsRNA-treated oilseed rape buds and anthers, leads to variable success in achieving a lethal phenotype in this pest species.…”
Section: Observed Rnai Sensitivities In Coleopteramentioning
confidence: 99%
“…In the present study, significant αCOP silencing at 3 d, in B. aeneus larvae fed dsαCOP at 2.5 µg/µL, substantiates the interpretation that this significant mortality was indeed the result of αCOP silencing. Willow et al (2021) also showed significantly greater mortality in B. aeneus adults chronically fed dsαCOP, compared to the mortality observed in short-term (3 d) treatments. Similar to the effect we observed in the present study regarding B. aeneus larvae fed dsαCOP 2.5 µg/µL-treated anthers, B. aeneus adults fed honey water at 1 and 3 µg dsαCOP/µL showed significant mortality at 6 d and 4 d, respectively (Willow et al, 2020b).…”
Section: Discussionmentioning
confidence: 76%
“…In a previous experiment comparing short-term-to chronic dsRNA feeding, B. aeneus adults that fed for 3 d on dsαCOP 2.5 µg/µL-treated anthers did not show significantly reduced survival (Willow et al, 2021). A significant reduction in B. aeneus adult survival was observed rather after 8 d of chronic feeding on dsαCOP 2.5 µg/µL-treated anthers, compared to the present study which showed significantly reduced survival at 4 d in larvae fed dsαCOP 2.5 µg/µL-treated anthers for 3 d. Thus, we here observed quicker RNAi-induced mortality in B. aeneus larvae, compared to what has been previously observed in B. aeneus adults that were fed comparable dsαCOP treatments.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This baseline study provides the first valuable insights on the broad applicability and transferability of RNA sprays over a geographic range in Europe (Mehlhorn et al, 2020). While the accessibility of phyllophagous pests by RNA sprays may seem trivial, a breakthrough was achieved by providing the first laboratory evidence that feeding dsRNA-coated oilseed rape buds to the pollen beetle Brassicogethes aeneus diminishes pollen beetle survival rate (Willow et al, 2021). This study is significant because many pathogens and pests that tremendously impact agriculture infect ears and buds rather than leaves.…”
Section: Significant Advances Of Rna Spray Controlling: Insectsmentioning
confidence: 99%